2017
DOI: 10.1186/s12864-017-4277-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and expression profiling of PDI family gene reveals function as abiotic and biotic stress tolerance in Chinese cabbage (Brassica rapa ssp. pekinensis)

Abstract: BackgroundProtein disulfide isomerase (PDI) and PDI-like proteins contain thioredoxin domains that catalyze protein disulfide bond, inhibit aggregation of misfolded proteins, and function in isomerization during protein folding in endoplasmic reticulum and responses during abiotic stresses.Chinese cabbage is widely recognized as an economically important, nutritious vegetable, but its yield is severely hampered by various biotic and abiotic stresses. Because of, it is prime need to identify those genes whose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 51 publications
2
40
0
1
Order By: Relevance
“…A glycine-rich RNA binding protein, member of a protein family involved in various stress responses [57], was only upregulated in the KNO 3 + series while an annexin, a member of a family of calcium-and phospholipid-binding proteins that has been linked to various stress responses [58], was upregulated in both groups. A protein disulfide isomerase, which is involved in the endoplasmic reticulum stress response that is also linked to salt stress [59,60], was only upregulated under salt stress in the KNO 3 + group. In summary, while some stress response pathways seem to be active in both series, others were only active either in non-nodulated plants growing on nitrate as N source, or in nodulated plants.…”
Section: Discussionmentioning
confidence: 99%
“…A glycine-rich RNA binding protein, member of a protein family involved in various stress responses [57], was only upregulated in the KNO 3 + series while an annexin, a member of a family of calcium-and phospholipid-binding proteins that has been linked to various stress responses [58], was upregulated in both groups. A protein disulfide isomerase, which is involved in the endoplasmic reticulum stress response that is also linked to salt stress [59,60], was only upregulated under salt stress in the KNO 3 + group. In summary, while some stress response pathways seem to be active in both series, others were only active either in non-nodulated plants growing on nitrate as N source, or in nodulated plants.…”
Section: Discussionmentioning
confidence: 99%
“…The segmental gene duplication event was marked based on the previously described criteria: the sequence alignment length covered more than 80% of the longer gene, and the identity of the aligned regions was over 70% (Jia et al 2017;Song et al 2017). The tandem duplicated genes were defined as two or more homologous genes located on one single chromosome with a distance of 100 kb without any intervening gene (Kayum et al 2017).…”
Section: Chromosomal Distribution and Gene Duplicationmentioning
confidence: 99%
“…Protein disulfide isomerases (PDIs) are enzymes found primarily in the endoplasmic reticulum (ER) in eukaryotes play a vital role in protein folding. The up-regulated levels of PDIs (A0A024FRN3, A0A1D5XQP7, A0A1D5XQP9, B9A8E3, F8THZ6, Q6JAB5, Q93XQ8) in the present study indicated the higher PDI activity (MF) and confirmed the active status of protein synthesis (Hayano et al ., 1995; Lv et al ., 2016; Kayum et al ., 2017) and higher resistance to abiotic stresses (Kayum et al ., 2017). This conclusion was strongly confirmed by the upregulation of 60S ribosomal protein L29 (A0A1D5RRD3), 40S ribosomal protein S12 (A0A1D5UFM0, A0A1D5UVS7) and Eukaryotic translation initiation factor 4B1 (Q9AUJ7) (Table S1).…”
Section: Discussionmentioning
confidence: 99%